2021
DOI: 10.3390/polym13132128
|View full text |Cite
|
Sign up to set email alerts
|

In-Line Rheo-Optical Investigation of the Dispersion of Organoclay in a Polymer Matrix during Twin-Screw Compounding

Abstract: The dispersion mechanisms in a clay-based polymer nanocomposite (CPNC) during twin-screw extrusion are studied by in-situ rheo-optical techniques, which relate the CPNC morphology with its viscosity. This methodology avoids the problems associated with post extrusion structural rearrangement. The polydimethylsiloxane (PDMS) matrix, which can be processed at ambient and low temperatures, is used to bypass any issues associated with thermal degradation. Local heating in the first part of the extruder allows test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…Therefore, the results indicate that for the material, geometry of the kneading blocks, and operating conditions used in the experiments, residence time is the predominant effect. Similar results have been recently reported for polymer/clay nanocomposites [ 59 ]. Therefore, and as anticipated, KB90-6 is the most efficient configuration for dispersion, as it is associated to higher residence times.…”
Section: Resultssupporting
confidence: 92%
“…Therefore, the results indicate that for the material, geometry of the kneading blocks, and operating conditions used in the experiments, residence time is the predominant effect. Similar results have been recently reported for polymer/clay nanocomposites [ 59 ]. Therefore, and as anticipated, KB90-6 is the most efficient configuration for dispersion, as it is associated to higher residence times.…”
Section: Resultssupporting
confidence: 92%
“…A possible explanation for the overestimation of W is given in Figure 1 c. At shear rates corresponding to those taking place in the squeezing chamber of the masticating unit, the slurry with 50 wt% dried biomass actually did not flow as predicted by Equation (1). Instead, strain localization and nonhomogeneous flow, which are ubiquitous in the rheology of dense suspensions, took place as suggested by the stress plateau at larger shear rates in Figure 1 c. Thus, a stress value on the order of 1 to 10 kPa should be considered to compute the mechanical work, which would then reach values between 7.5 and 126 kJ·kg −1 and compare to mechanical works computed for the melt mixing of, for example, polymer composites [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it was established that for higher degrees of exfoliation and dispersion, by melt processing, often required an adequate residence time in the extruder and an appropriate shear profile. These results suggested that melt processing technique, using a continuous melt mixing procedure in a twin‐screw extruder, can result in comparatively higher levels of exfoliation and dispersion of fillers in polymer nanocomposites, such as those containing, clay, [ 22 ] carbon nanotubes, [ 24 ] and graphite, [ 25 ] without chemical modifications, or by using compatibilizers. However in this context, so far no report(s) on the exfoliation and dispersion of h‐BN in the polymeric matrices via melt‐processing using continuous melt‐mixing processes in a twin‐screw extruder can be found in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a lot of attention [16][17][18][19][20][21][22][23][24][25][26][27] has been also paid to the exfoliation and dispersion characteristics of oneand/or two-dimensional materials, formed in polymer melts, through continuous melt-mixing processes, such as via twin-screw extrusion. For example, Cho and Paul [17] prepared polymer organoclay nanocomposites through melt compounding, using a typical co-rotating twin screw extruder.…”
mentioning
confidence: 99%
See 1 more Smart Citation